O46. X-ray, γ and neutron irradiated spherical gold nanoparticles in human breast epithelium and human skin keratinocyte cells. (September 2016) - de Kock, M.; Nel, J.; Engelbrecht, M.; Slabbert, J.P.
Abstract : Introduction: Auger electron-emitting radiopharmaceuticals are attractive for nano-irradiation therapy, given that DNA of malignant cells is selectively targeted. The limited penetration of kV X-rays, in comparison to megavoltage (MV), is a challenge of radiotherapy and gold nanoparticles (AuNPs) have been identified as effective radiosensitisers following bombardment with low energy (e.g. 200–500 keV) radiation. Materials and methods: AuNPs were synthesised via the 'green nanotechnology' method using cinnamon (Cinn-), red-speckled beans (RSB-) and soybeans (SB-) as phytochemical reservoirs for the reduction and stabilisation of gold salts to AuNPs. Skin (HaCaT), breast (MCF10A), and malignant breast (MCF7) cell lines were treated with each AuNP type, and radiated with either 2 Gy 60 Co γ - or X-rays, or 1 Gy p(66)/Be(49) neutrons. The cytokinesis-block micronucleus assay was used to determine the presence of micronuclei (MNi) within binucleated cells. Results: An overall increase in MNi numbers were recorded for non-malignant HaCaT and MCF10A cells treated with AuNPs and exposed to X-ray radiation, whilst 60 Co γ -radiation caused less MNi. However, AuNPs served as radioprotective devices within the neoplastic MCF7 cell line wherein MNi numbers were much less after incubation with AuNP types and X-ray exposure. Furthermore, the RSBGA-AuNP seemed to have the greatest effect on MNi occurrence: the nanoparticle caused a sensitisation effect in HaCaT and MCF10A cells to γ - and neutron radiation, whilst serving as a radioprotector against X-ray exposure. However, for the cancerous MCF7 cells, RSBGA-AuNPs caused radioprotection against γ -radiation, whilst sensitising the cells to X-ray and neutron radiation after 24h incubation with AuNPs. Conclusion: Several explanations were provided for the above occurrences, including: the size of the AuNPs, the failure of the AuNPs to penetrate the nuclear membrane, the formation of possible autophagosomal and lysosomal bodies sequestering the AuNPs, the effect AuNPs have on the cell cycle, and the radical scavenging capabilities of the phytochemical-coated AuNPs.